Review of An Introduction to Atonal Music Analysis - Mohammad Reza Azadehfar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article is a review of the book An Introduction to Atonal Music Analysis by Amin Honarmand, published by University of Tehran in 2014. This book consists of four main chapters. It begins by general issues on the analysis of atonal music in chapters one to three and focuses on structure of dodecaphonic music in the last chapter. Even though the roots of atonal music are not in Iran, one may doubt why the author has chosen to write a book in this issue rather than translating readily available books written by Western scholars to Persian. It seems that the main reason for choosing to write a new text rather than translating is the need of Persian students for a simplified source in this issue. The review of this book showed that Honarmand has been somehow successful and the output is clear enough for students who need basic knowledge of music analysis of atonal music. The review of this book also revealed that one may not find all aspects of atonal music in this book, and it still needs further resources to make a complete analysis of atonal music, particularly in aspects of harmony and orchestration. However, the book perfectly disuses pitch classes and pitch collection issues and to a good extent dodecaphonic music analysis. Before reading this book, the reader needs good knowledge of tonal music and related issues of that kind of music in order to make a better sense of absence of tonality in configuration of atonal music.